Metformin improves in vivo and in vitro B cell function in individuals with obesity and Type-2 Diabetes. Issue 20 (9th May 2017) - Diaz, Alain; Romero, Maria; Vazquez, Thomas; Lechner, Suzanne; Blomberg, Bonnie B.; Frasca, Daniela
Highlights: The effects of Metformin on B cell function is not well known. T2D patients taking Metformin have optimal influenza vaccine responses. Metformin in vitro increases class switch and reduces B cell inflammation. Metformin in vitro increases AMPK activation. Abstract: Metformin (MET), the first-line medication for Type-2 Diabetes (T2D), has been shown to reduce chronic inflammation indirectly through reduction of hyperglycemia, or directly acting as anti-inflammatory drug. The effects of MET on B lymphocytes is uncharacterized. In the present study, we measured in vivo and in vitro influenza vaccine responses in 2 groups of T2D patients: recently diagnosed but not taking anti-diabetic drugs, and patients taking MET. Results show that B cell function and vaccine responses, hampered by obesity and T2D, are recovered by MET. Moreover, MET used in vitro to stimulate B cells from recently diagnosed T2D patients is also able to reduce B cell-intrinsic inflammation and increase antibody responses, similar to what we have seen in B cells from patients taking MET, who show increased responses to the influenza vaccine in vivo . These results are the first to show an effect of MET on B cells.